Strategi Bertahan UMKM di Tengah Pandemi Covid-19 - Turmono (Jurnal Teknologi dan Bisnis, 2021)
The world is being hit by a covid-19 pandemic including Indonesia. To break the chain of spreadingof the virus, The government ask everypeople to stay at home. This situation has an impact on economic instability and affected to SMEs. Therefore, a survival strategy for SMEs is needed to continuous their business during the pandemic. This study used qualitative analysis with exploratory yanf participatory observation techniques. The result of this study recommend 4 ways a survival strategy for SMEs. Therea are using e-commerce for business, using digital marketing, improving product and service qualityand optimizing customer relationship marketing. The result of this study are important to be understood and adopted by SMEs and hopefully they always responsive and adjusting to business environment to survive.